2016
DOI: 10.1158/1535-7163.mct-16-0136
|View full text |Cite
|
Sign up to set email alerts
|

Covalent Targeting of Fibroblast Growth Factor Receptor Inhibits Metastatic Breast Cancer

Abstract: Therapeutic targeting of late-stage breast cancer is limited by an inadequate understanding of how tumor cell signaling evolves during metastatic progression and by the currently available small molecule inhibitors capable of targeting these processes. Herein, we demonstrate that both β3 integrin and fibroblast growth factor receptor-1 (FGFR1) are part of an epithelial-mesenchymal transition (EMT) program that is required to facilitate metastatic outgrowth in response to fibroblast growth factor-2 (FGF2). Mech… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
70
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 67 publications
(80 citation statements)
references
References 35 publications
(51 reference statements)
8
70
0
Order By: Relevance
“…These data are supported by previous findings that demonstrate an FGF2 signaling loop is at play in basal-like breast cancer [26]. Furthermore, together with our recent study we conclude that FGF2 and β3 integrin are part of an EMT signature that contribute to FGFR1-mediated drug resistance and metastatic progression [15]. Along these lines, recent clinical data indicate that unlike the autoactivation of Her2 upon gene amplification, FGFR1 amplification alone is insufficient to predict patient response to FGFR inhibitor therapy [27].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data are supported by previous findings that demonstrate an FGF2 signaling loop is at play in basal-like breast cancer [26]. Furthermore, together with our recent study we conclude that FGF2 and β3 integrin are part of an EMT signature that contribute to FGFR1-mediated drug resistance and metastatic progression [15]. Along these lines, recent clinical data indicate that unlike the autoactivation of Her2 upon gene amplification, FGFR1 amplification alone is insufficient to predict patient response to FGFR inhibitor therapy [27].…”
Section: Discussionsupporting
confidence: 92%
“…However, the role of FGFR may have been underestimated in these studies due to the use of Type I ATP competitive FGFR kinase inhibitors. Indeed, the findings herein and our recently published studies clearly point to the enhanced efficacy of covalent FGFR inhibitors as compared to ATP competitive molecules [15]. Furthermore, our utilization of both the HMLE and BT474 models of Her2+ breast cancer clearly demonstrate that enhanced FGFR1 expression when in the presence of FGF ligand is sufficient to facilitate resistance to Lapatinib treatment.…”
Section: Discussionsupporting
confidence: 70%
“…Moreover, during EMT and the reverse mechanism known as mesenchymal-epithelial transition (MET), FGFR1 was found to be upregulated upon stimulation with TGF-β1 in a breast cancer cell model [135]. A novel study showed that FGFR is associated to E-cadherin, but under expression of β3 integrin subunit, which is upregulated upon TGF-β stimulation [136], FGFR dissociates from E-cadherin and associates with β3 integrin, leading to Erk1/2 phosphorylation in response to FGF2 [137,138]. Bone morphogenic protein 7 (BMP-7) is a cytokine that belongs to the TGF-β superfamily [139] and was shown to induce invasion in hepatocellular carcinoma cells [140], breast cancer cells [141] and chondrosarcoma cells [142].…”
Section: Hallmarking Cancermentioning
confidence: 99%
“…Luciferase expressing 4T1 and HMLE cells were transformed via overexpression of Her2 and their mesenchymal variants were described previously 20,34 . Ca1a cells were kindly provided by Dr. Fred Miller (Wayne St. University).…”
Section: Reagentsmentioning
confidence: 99%